Bound to lose, bound to win? The financial crisis and the informal-formal sector earnings gap in Serbia - Niels-Hugo Blunch (IZA Journal of Labor & Development, 2015)
While the informal sector has received widespread attention in academic and policy arenas in recent decades, knowledge gaps and controversies remain. By examining the incidence and determinants of the formal-informal sector earnings gap for adult male dependent employees using two identical, nationally representative labor force surveys for Serbia-one just prior to the impact of the recent international financial crisis and one about a year into the crisis-for three alternative measures of informality, this paper adds to our understanding in several dimensions. Among the main results is the finding of a substantively large formal-informal sector earnings gap (favoring the formal sector)-across three alternative informality measures-which appears to have decreased substantially overall following the crisis. Additional results suggest that formal sector workers are concentrated in better paying industries and occupations and have more education and other favorable characteristics than informal sector workers, and at the same time also have higher returns to their (already favorable) characteristics overall, with education and part-time status consistently among the main drivers of the observed gap.
Keywords: I24; J31; J42; J46; 330; Formal-informal sector earnings gap; Labor market segmentation; Earnings decomposition; Detailed earnings decomposition; International financial crisis; Serbia